PENGEMBANGAN SOFT SKILL TANGGAP BENCANA KEBAKARAN SEBAGAI UPAYA PREVENTIF BAGI SISWA SD - Dyah Puspita Indah Budi Sari Wulan; Nurleila Jum'ati; Risca Ayu Rachmania; Nur Aini Azizah; Mochamad Syahrul Gunawan; Raihana Raihana; Okky Irfanto (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2021)
Indonesia is one of the countries that are prone to disasters, one of the vulnerable victims of disasters is children. There is fire data in the educational environment in the city of West Surabaya and data on potential fires in the western region of Surabaya. With these data, it encourages the holding of community service activities in the form of improving soft skills towards mitigation, preparedness for fire disasters. The development of soft skills to respond to fire disasters as a preventive effort in children from an early age is carried out in students of AlKautsar Elementary School Surabaya. Methods of community service are observation, pretest, socialization, mentoring, forming a fire fighter community and posttest. Based on the average value of knowledge obtained by students is quite high after joining the program compared to before. By following the improvement of soft skills, students gain knowledge and strengthen the education of character, literacy development as well as fostering self-efficacy students. With self-efficacy, students acquire such knowledge for themselves and can educate the surrounding environment. It is hoped that for the sustainability of the program can be formed a community that is accommodated in an extracurricular fire fighter involving parties: schools, parents of students or representatives of school committees and students and all other school residents.